2018
DOI: 10.1007/s00208-018-1775-8
|View full text |Cite
|
Sign up to set email alerts
|

Extremal functions for Morrey’s inequality in convex domains

Abstract: For a bounded domain Ω ⊂ R n and p > n, Morrey's inequality implies that there is c > 0 such thatfor each u belonging to the Sobolev space W 1,p 0 (Ω). We show that the ratio of any two extremal functions is constant provided that Ω is convex. We also show with concrete examples why this property fails to hold in general and verify that convexity is not a necessary condition for a domain to have this feature. As a by product, we obtain the uniqueness of an optimization problem involving the Green's function fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…u l,j jq(x) = Λ l,j and by making j → ∞ we obtain µ l ≤ lim inf j→∞ Λ l,j , concluding thus the proof of (19). We say that u ∈ W 1,lp(x) 0…”
Section: Extremal Functions Formentioning
confidence: 62%
See 2 more Smart Citations
“…u l,j jq(x) = Λ l,j and by making j → ∞ we obtain µ l ≤ lim inf j→∞ Λ l,j , concluding thus the proof of (19). We say that u ∈ W 1,lp(x) 0…”
Section: Extremal Functions Formentioning
confidence: 62%
“…We also show in Section 4, by using arguments developed in [19], that µ l is achieved at u if, and only if,…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In recent work, we showed that there is a smallest C = C * > 0 so that Morrey's inequality holds with C * and that there exist nonconstant functions for which equality is attained in (1.2) [19]. We will call these functions Morrey extremals.…”
Section: Ryan Hynd and Francis Seuffertmentioning
confidence: 99%
“…While C * and the corresponding Morrey extremals are not explicitly known, many qualitative properties of these functions have been identified. In particular, Morrey extremals which satisfy (1.3) and (1.4) are known to be unique, axially symmetric about the x n −axis and antisymmetric about the x n = 0 plane ( [19], Section 3 and 6). We established this in our previous work by relying on a uniqueness property of solutions of (1.5).…”
Section: (14)mentioning
confidence: 99%